A Theology of Social Engagement for Evangelicals: The Reign of God and Social Transformation - Emanuel, Frank (Université Saint-Paul / Saint Paul University, 2015)
This thesis emerges from my own concerns about how North American evangelicals approach social and environmental challenges. As an evangelical pastor I continue to be troubled by the lack of attention paid by evangelicals to actually making the world a better place. I began by investigating the theological reasons behind the evangelicals’ lack of commitment to social amelioration. In those studies I discovered eschatological concepts that shaped the evangelicals’ attitudes towards the socio-political world. Therefore, this thesis is an exploration of a cluster of related, yet complex subjects: evangelicals, eschatology, and social engagement. The primary aim of this thesis is to address the eschatology that shapes the approaches evangelicals take in engaging with the social and environmental challenges of our day. This thesis begins by describing the historical roots of contemporary evangelical eschatological theology. Having described the complexity of evangelical eschatology, the second chapter offers a sustained reflection on the neo-evangelical critique of the pessimistic eschatological theologies that emerged from the Fundamentalist movement. Through the neo-evangelical critique, this thesis then analyzes some of the more significant problems with contemporary evangelical social engagement. Those deficiencies are brought into dialogue with the Hope Theology of Jürgen Moltmann. Moltmann’s proposed eschatological theology coincides with the neo-evangelical proposal of an inaugurated-enacted eschatology. This inaugurated-enacted eschatological theology is then used in the construction of my own theological proposal for a theology of social engagement for evangelicals. This theological proposal identifies several key ideas posited by an inaugurated-enacted eschatology and then applies these ideas to evangelical notions of biblicism, crucicentrism, conversionism, and activism. A final chapter explores the potential of my proposed theology of social engagement for overcoming deficiencies in evangelical environmental theologies. This final chapter demonstrates the efficacy of my proposed evangelical theology of social engagement for improving evangelical approaches to social and environmental amelioration. Throughout this thesis I claim that evangelical can and must do a better job of addressing the social and environmental issues of our day. My contribution is to offer an eschatological framework for improving evangelical theologies of social engagement.
Keywords: Eschatology; Evangelicalism; Social Justice; Political Theology